INVESTASI AKOMODASI WISATA YANG PALING PRODUKTIF DI KAWASAN STRATEGIS PARIWISATA NASIONAL (KSPN) GILI TRAMENA - I Wayan Priyana Agus Sudharma (Nusantara Hasana Journal, 2023)
North Lombok Regency (KLU) has two National Tourism Strategic Areas (KSPN) as outlined in Government Regulation no. 50 of 2011 concerning the National Tourism Development Master Plan for 2010 – 2025, namely the KSPN Gili Tramena and KSPN Rinjani. The KLU tourism sector has still not fully recovered after experiencing earthquakes in 2018 and the Covid-19 pandemic so that the large tourism potential that exists in KLU is something that can attract investors. To determine the most optimal type of tourism accomodation that can be built by investors, the Highest and Best Use (HBU) analysis is an analysis that is often used. The results of the HBU analysis show that of the three alternatives tested, the private villa produced the highest NPV value of IDR 19,495,000,000 and the land value of IDR 5,110,160,000 or an increase of 133.87% from the value of the land before it was developed.